Interband impact ionization by terahertz illumination of InAs heterostructures - Markelz, A. G.; Asmar, N. G.; Brar, B.; Gwinn, E. G. (Applied Physics Letters, 1996)
Experimental studies of InAs heterostructures illuminated by far-infrared (FIR) radiation reveal an abrupt increase in the charge density for FIR intensities above a threshold value that rises with increasing frequency. We attribute this charge density rise to interband impact ionization in a regime in which omega tau(m) similar to 1, where tau(m) is the momentum relaxation time, and f=omega/2 pi is the FIR frequency. The dependence of the density rise on the FIR field strength supports this interpretation, and gives threshold fields of 3.7-8.9 kV/cm for the frequency range 0.3-0.66 THz. (C) 1996 American Institute of Physics.
Keywords: energy; far-infrared excitation; inas/alsb quantum-wells; inplane; modulation; Physics